Linear Immunoglobulin a Bullous Dermatosis in Children - Mori, Francesca; Saretta, Francesca; Liotti, Lucia; Giovannini, Mattia; Castagnoli, Riccardo; Arasi, Stefania; Barni, Simona; Mastrorilli, Carla; Pecoraro, Luca; Caminiti, Lucia; Marseglia, Gian Luigi; Barbaud, Annick; et al. (Frontiers in Pediatrics, 2022)
Linear Immunoglobulin A Bullous Disease (LABD) is a rare dermatosis whose pathomechanisms are not yet completely understood. LABD has different features characterizing adults and children in terms of potential triggers, clinical manifestations, and prognosis. The aim of the present study was to review all neonatal and pediatric cases of LABD and summarize the major characteristics. Childhood LABD is mainly idiopathic with a benign prognosis. Drugs appear to be triggering factors of pediatric LABD. Neonatal cases are difficult to differentiate from infectious diseases and usually have a poor prognosis. It has been proposed that various stimuli (e.g., infections, drugs, inflammatory diseases, trauma) can activate autoimmune responses through antigen mimicry and epitope spreading. The gold standard for the diagnosis is based on direct immunofluorescence. Prognosis is generally favorable but often depends on the prompt dermatological diagnosis, treatment and follow-up guaranteed by a multidisciplinary team, including paediatricians for this group of age.